Alternative machining procedures of hardened steels - János, Kundrák (Manufacturing Technology Journal, 2011)
This paper outlines the hard machining procedures, their applicability, the increase of their efficiency and the possibilities provided through their combination. It focuses on the advantages of the cutting and grinding compared to each other and also on the cases when it is appropriate to apply them or possibly combine them.
Keywords: grinding; hard turning; alternative machining; hardened steel